Credibility And Rhetoric Of Agus Muhammad Iqdam Kholid's Dakwah - Adibah Husnaa Rihadatul Aisy (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2026)
As a preacher, high credibility is essential to gain trust in delivering Islamic preaching material to the public. Likewise, effective rhetoric, or the way in which Islamic preaching material is delivered, will also determine a preacher's success in delivering his preaching, ensuring it is easily accepted and implemented by his audience. Agus Muhammad Iqdam Kholid, commonly known as Gus Iqdam, is a young preacher from East Java. He not only preaches in congregations but also on social media. In delivering his preaching material, he draws on relevant sources, such as the Quran and Hadith, as well as on books he has mastered. Gus Iqdam's delivery of his preaching material uses easily understood language and often uses his local language, making his preaching highly sought after by the public, including the younger generation and others. This research employed qualitative methods, analyzing Gus Iqdam's preaching content, netizen comments, and news sources from other social media platforms. The data sources used were Gus Iqdam's profile, his preaching, and audience responses in the form of comments and posts on social media. The results of this study indicate that Gus Iqdam possesses credibility components such as trustworthiness, expertise, authority, charisma, and good morals.